Business Intelligence (BI) System for Budgeting and Customer Satisfaction - Chi, Aung Nay (International Journal of Information Technology and Computer Science Applications, 2023)
This research is about a casino company that wishes to use Business Intelligence (BI) system to solve their budgeting problems while attracting customers. They provided the dataset required to analyse their two casino branches and find what actions that they need take, with the help of visualizations. After analysing the visualizations, it was clear that there were many machines that their customers are not found of and that video machines are the most popular among the three types of machines. The least played type of machine was vpoker and only two manufactures provide them with the machines. The likely reason for people do not playing vpoker is that it requires mental strength and mathematics. It was also clear that customers come to the casinos in April, possibly due to holidays. With the help of new technologies, they can gather more information from their customers, without upsetting them and increasing the security to prevent vandalism and destruction of property by angry customers.